Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1600-0838.2008.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid administration alters the mechanical properties of isolated collagen fascicles in rat‐tail tendon

Abstract: Overload tendon injuries are frequent in recreational and elite sports. The optimal treatment strategy remains unknown, but local administration of corticosteroids is one common treatment option. The direct effects of the corticosteroid administration on the tissue are not fully understood. The present study examined the biomechanical effects of intratendinous corticosteroid injections on healthy rat-tail tendon collagen fascicles. A total of 24 Wistar male rats were divided into (A) a corticosteroid group whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 51 publications
(84 reference statements)
1
10
1
Order By: Relevance
“…Because tendons are hierarchical structures, it is possible for viscoelastic effects to emerge at various levels of organization; therefore, it is important to consider the benefits and limitations of investigating viscoelasticity solely at the fascicle level. A benefit of tendon fascicles studies is the abundance of rat tail tendon fascicle studies, thereby providing measurements that are directly comparable to our own (Hansen et al, 2002;Haraldsson et al, 2009;Legerlotz et al, 2010). For example, Elastic Moduli obtained in this study were consistent with previously published values.…”
Section: Limitationssupporting
confidence: 86%
See 2 more Smart Citations
“…Because tendons are hierarchical structures, it is possible for viscoelastic effects to emerge at various levels of organization; therefore, it is important to consider the benefits and limitations of investigating viscoelasticity solely at the fascicle level. A benefit of tendon fascicles studies is the abundance of rat tail tendon fascicle studies, thereby providing measurements that are directly comparable to our own (Hansen et al, 2002;Haraldsson et al, 2009;Legerlotz et al, 2010). For example, Elastic Moduli obtained in this study were consistent with previously published values.…”
Section: Limitationssupporting
confidence: 86%
“…As a result, the maximum strain achieved across all trials was less than 1% Additionally, in our preliminary tests, we were not able to exceed 1.5% strain without failure. Although previous studies have reported up to 4% (Rigby et al, 1959) strain and 12 MPa of stress before indication of failure of tendon fascicles (Haraldsson et al, 2009), we were not able to replicate these results. It is likely that our method of testing caused concentrations of stress and/or strain in the tendon fascicle near the clamp, resulting in failure at much lower strains and stresses than previously reported.…”
Section: Limitationscontrasting
confidence: 78%
See 1 more Smart Citation
“…An in vivo study found that corticosteroids negatively affected biomechanical properties and caused pathological changes in rat tendons . Hugate et al showed the absence of significant differences in the maximum failure loads between a corticosteroid group and a saline group, 4 weeks after injection .…”
Section: Discussionmentioning
confidence: 99%
“…Three specimens were tested for each mouse tail. A more detailed description of the instrumentation and the mechanical testing procedure is available in previous publications (29,30).…”
Section: Methodsmentioning
confidence: 99%